When close is not close enough: a comparison of endogenous and recombinant biomarker stability samples. (June 2015) - Fraser, Stephanie; Fleener, Catherine; Ogborne, Kevin; Soderstrom, Catherine
Dr Stephanie Fraser is an Associate Research Fellow in the Pharmocokinetics, Dynamics and Metabolism department at Pfizer, Groton, Connecticut. Since 2010 she has led a small but ambitious group of scientists that provide ligand-binding and immunoassay-based support to clinical biomarker programs across multiple therapeutic areas. Prior to joining Pfizer, Stephanie spent 5 years in preclinical toxicology at Charles River Laboratories where she managed a flow cytometry laboratory. She received her PhD in cellular and molecular biology from the University of Nevada, Reno in 1999 and has since focused on biomarker development and fit-for-purpose bioanalytical assays. Stability for biomarkerassays should be established during method validation using actual samples. Due to contradictory reference papers and a near absence of biomarker guidance documents actual samples are commonly replaced with spiked validation samples. This practice often fails to identify the stability of the endogenous biomarker. Spiked QC and endogenous biomarker sample data were collected for two immunoassays, TGF- β1 and IL-13. Following one freeze/thaw cycle purified TGF-β1 recovery ranged between 87-110% whereas endogenous TGF-β1 was 5-96%. Spiked recombinant IL-13 validation samples were stable for 4 months, whereas placebo samples were stable for 15 months. In these two cases stability established with purified and recombinant protein did not reflect the endogenous protein stability.